Diazotrophy Drives Primary Production in the Organic-Rich Shales Deposited Under a Stratified Environment During the Messinian Salinity Crisis (Vena del Gesso, Italy) - Isaji, Yuta; Kawahata, Hodaka; Takano, Yoshinori; Ogawa, Nanako O.; Kuroda, Junichiro; Yoshimura, Toshihiro; Lugli, Stefano; Manzi, Vinicio; Roveri, Marco; Ohkouchi, Naohiko (Frontiers in Earth Science, 2019)
Density stratification between freshwater and brine is periodically formed during massive evaporation events, which often associates deposition of organic-rich sediments. Here, we investigated phototrophic communities and nitrogen cycle during the deposition of two organic-rich shale beds of gypsum–shale alternation, representing the initial stage of the Messinian salinity crisis (Vena del Gesso, Northern Apennines, Italy). The structural distributions and the carbon and nitrogen isotopic compositions of geoporphyrins show a common pattern in the two shales, indicating the predominance of a particular phototrophic community under freshwater–brine stratified conditions. The ~6‰ difference in δ13C of total organic carbon between PLG 4 and 5 shales was associated with similar shift in δ13C of the porphyrins derived from chlorophyll c, suggesting that the eukaryotic algae producing chlorophyll c were the major constituent of the phototrophic community. Importantly, these porphyrins show δ15N values (−7.6‰ to −4.7‰) indicative of N2-fixation. We suggest that nitrate-depletion in the photic zone induced the predominance of diazotrophic cyanobacteria, which supplied new nitrogen for the chlorophyll c-producing eukaryotic algae. The large difference in the δ13C values of porphyrins and total organic carbon between PLG 4 and 5 shales are interpreted to reflect the depth of the chemocline, which fluctuates in response to changes in the regional evaporation–precipitation balance. Such variation in the chemocline depth may have dynamically changed the mode of the nitrogen cycle (i.e., nitrification–denitrification–N2-fixation coupling vs. phototrophic assimilation of ammonium) in the density-stratified marginal basins during the Messinian salinity crisis.